1985
DOI: 10.1530/acta.0.1080231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin on altered mineral and vitamin D metabolism in streptozotocin-induced diabetes

Abstract: In order to ascertain whether or not abnormal mineral and vitamin D metabolism in diabetes can be reversed by insulin therapy, plasma calcium, ionized calcium, phosphorus, parathyroid hormone (PTH) and vitamin D metabolites were measured in control, streptozotocin (STZ) diabetic and insulin-treated diabetic rats. Blood glucose levels in diabetic rats treated with insulin decreased to normal. The low plasma calcium and ionized calcium levels in diabetic rats were found to be normal in insulin-treated diabetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In streptozotocin-induced diabetic rats with b cell destruction, plasma calcium levels, DBP, circulating vitamin D, and bone mass were reduced [76][77][78]. After insulin therapy, plasma 25(OH)D3 was fully restored [77].…”
Section: Effect Of Vitamin D On Insulin Secretionmentioning
confidence: 97%
“…In streptozotocin-induced diabetic rats with b cell destruction, plasma calcium levels, DBP, circulating vitamin D, and bone mass were reduced [76][77][78]. After insulin therapy, plasma 25(OH)D3 was fully restored [77].…”
Section: Effect Of Vitamin D On Insulin Secretionmentioning
confidence: 97%
“…In this model, STZ destroyed the β cells of the pancreas islet, and this results in the induction of type 1 DM. However, STZ might also influence the kidney and liver 7,8) . It was of note that these rats showed extremely high fasting blood glucose levels, on the order of 421-573 mg/dL 9,10) .…”
Section: Experimental Animalsmentioning
confidence: 99%
“…These osteoblastic functions are regulated by la,25-dihydroxyvitamin D, (1,25(OH),D,), and acute and chronic streptozotocin (STZI-induced diabetes has been shown to decrease plasma 1,25(OH),D3 levels (Schneider et al, 1977;Schedl et al, 1978;Hough et al, 1981;Shires et al, 1981;Ishida et al, 1985). Schedl et al (1978) suggested that a primary result of insulin deficiency in diabetes is a n abnormality in vitamin D, metabolism leading to impaired 1,25(OH),D, production.…”
Section: Structural and Cytochemical Changes Of Osteoblasts During Exmentioning
confidence: 99%